A decentralized approach for optimal reactive power dispatch using a Lagrangian decomposition method - Granada, M.; Rider, Marcos J. [UNESP]; Mantovani, J. R. S. [UNESP]; Shahidehpour, M. (Elsevier B.V. Sa, 2012)
This paper addresses a decentralized approach based on Lagrangian decomposition method for the optimal reactive power dispatch (ORPD) problem in multi-area power systems. This approach allows an independent but coordinated operation of each regional operator (RO) of the electrical power system and aims to preserve the confidentiality of the network data in each area. Some convergence properties and particular drawbacks of the decentralized ORPD problem are identified and the feasibility of applying the decomposition technique to ORPD problem is analyzed. The IEEE RTS-96 system and a 354-bus system (composed of three IEEE 118-bus systems) are used to show the operation and effectiveness of the decomposition method and the convergence behavior of the decentralized ORPD proposed. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Decomposition methods; Multi-area power systems; Optimal reactive power flow; Decentralized coordination